Jurisdiction And Applicable Law in Cyber - Delicts: A Comparative Private International Law Study - Gayani, H. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
The rise of cyber-delicts including online defamation, data breaches, identity theft, cyberstalking, and AI-generated harms challenges traditional Private International Law (PIL) paradigms rooted in territorial boundaries. These doctrines, designed for physical wrongful acts, struggle to effectively regulate digital misconduct characterized by instantaneity, borderlessness, and anonymity. This study conducts a comparative analysis of jurisdiction and applicable law in cyber-tort disputes across the United Kingdom, European Union, United States, South Africa, and Sri Lanka. The UK primarily applies common law connecting factors alongside its Civil Procedure Rules; the EU relies on structured frameworks under Brussels I Recast and Rome II; the US employs constitutional minimum contacts and effects-based tests; South Africa maintains the lex loci delicti rule; and Sri Lanka, with its hybrid legal system, currently lacks a coherent conflict-of-laws regime tailored to cyber-torts. Key challenges identified include defining the “place of harm” in cyberspace, addressing the multiplicity of publication in online defamation, assessing the adequacy of traditional territorial tests, and mitigating risks of forum shopping and jurisdictional overreach. Through doctrinal and comparative methods, this research critically examines whether existing PIL principles suffice for digital-era violations or whether new or adapted frameworks are necessary. It advocates for a recalibrated approach incorporating targeting, foreseeability, digital presence, and enhanced party autonomy to better accommodate cyber-delicts. Drawing on comparative insights, the study proposes a principled model for Sri Lanka that aims to improve predictability, fairness, and technological adaptability in cross-border cyber-tort litigation. By bridging classical PIL with contemporary technological challenges, this research offers a reform-oriented contribution to legal scholarship and practical guidance for courts and policymakers navigating the complex landscape of cyber litigation.
Keywords: Cyber-delicts; Private international law; Comparative study